Analysis of Teenagers' Receptions About Free Association in the "Little Mom" Series on We Tv - Ria Ade Nasti; Asnawati Asnawati; Anis Endang SM (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2022)
Film is one of the mass communication media that has a major influence on the wider community. The Little Mom film series directed by Guntur Soehardjanto tells the story of teenage pregnancy which is the result of promiscuity. The purpose of this study was to analyze adolescents' reception of promiscuity in the Little Mom series. This study used a qualitative descriptive research method using Stuart Hall's reception analysis. It is expressed in three possible positions, namely dominant hegemony, negotiating position, and oppositional position carried out by the subject under study. Reception analysis refers to the study of the meaning of production and audience experience in relation to interacting with media texts. Stuart Hall explained that reception can be described through a process called encoding-decoding. Encoding is the process of translating the message carried out by the source while decoding is the recipient's attempt to translate the message obtained from the source. The research data collection technique was Roland Bartes' semiotic analysis of 5 scenes and structured interviews with 4 informants in Marga Sakti Sebelat District who were selected by purposive sampling to determine informant criteria and snowball sampling to determine the four informants in the study. The results of the study show that in the first scene, second scene, and third scene, the informants are dominated by oppositional positions. In the fourth scene, informants 1, 2 and 4 are in an oppositional position and informant 3 is in a negotiating position. In the fifth scene, informants 1, 3 and 4 are in an oppositional position and informant 2 is in a negotiating position. There are no informants who are in a position of dominant hegemony.